A first approach to chalcid wasps (Hymenoptera, Chalcididae) of the entomological museum UNAB with new records for Colombia - Alba Lucia Pérez-Benavides; Francisco Serna (Agronomía Colombiana, 2019)
The entomological museum of Universidad Nacional, Faculty of Agricultural Sciences, Bogota, (UNAB) Colombia, conserves several arthropod collections. These collections are considered of great interest to several agricultural and silvicultural production systems in the eastern Andes and the nearby Amazon region (Caqueta and Putumayo provinces) of the country. As a contribution to the knowledge of the diversity of parasitoid wasps associated to agroecosystems (cacao in agroforestry systems, mainly) of these geographical areas, the current research presents a first approach to the study of Chalcididae wasps at this museum. The curatorial status was organized, the represented genera identified, and the geographic occurrences in extension and altitude graphically represented. The Central Taxonomic Collection (CTC) is the main collection at UNAB. It contains 214 specimens of the family Chalcididae that correspond to the genera Brachymeria, Conura, Dirhinus, Haltichella, Notaspidium, Stypiura, Ecuada, and Parastypiura, with records from 17 provinces. The genera Ecuada and Parastypiura, as well as 11 species of Conura, are recorded for the country for the first time.